Downregulation of Angiogenesis Factors, VEGF and PDGF, after Rapid IgE Desensitization and Oral Immunotherapy in Children with Food Allergy. (2nd June 2014) - Poza-Guedes, Paloma; Barrios, Yvelise; Fuentes, Victoria; Franco, Andres; Sánchez-Machín, Inmaculada; Alonso, Elena; González Pérez, Ruperto; Infante, Sonsoles; Zapatero, Lydia; Matheu, Víctor
Abstract : Background . Angiogenesis has a key role in several conditions and is regulated by several factors such as the platelet-derived growth factor (PDGF) or the vascular endothelial growth factor (VEGF). The goal of this study was to investigate the possible role of PDGF and VEGF in a group of patients with severe food allergy. Methods . We design a prospective longitudinal study (n = 30 ) with patients with persistent cow's milk proteins (CMP) allergy. After achieving a CMP rush desensitization protocol, a clinical followup including SPT and blood samples to determine sIgE, protein levels, PDGF, and VEGF-A and a panel of the most representative Th1, Th2, Treg, and Th17 cytokines were also monitored. Results . Baseline levels of PDGF and VEGF in the CMP allergic patients (1170 pg/mL and 253 pg/mL) were different compared to those nonallergic CMP control subjects (501 pg/mL and 108 pg/mL). Both PDGF and VEGF were significantly downregulated (P < 0.05 ) 6 months after completion of the CMP desensitization process and remained significantly decreased 12 months later. Conclusion . The present study shows a significant increase of PDGF and VEGF in anaphylaxis suffering children compared to a control group. Interestingly, both VEGF and PDGF were significantly downregulated after completing a full CMP rush IgE desensitization.